The Alzheimer’s Disease Activities of Daily Living International Scale (ADL-IS) - Reisberg, Barry; Finkel, Sanford; Overall, John; Schmidt-Gollas, Norbert; Kanowski, Siegfried; Lehfeld, Hartmut; Hulla, Franz; Sclan, Steven G.; Wilms, Hans-Ulrich; Heininger, Kurt; Hindmarch, Ian; Stemmler, Mark; et al. (International Psychogeriatrics, 2001)
Background: Activities of daily living (ADL) deficits are integral components of dementia disorders, and ADL measures are among the most robust markers of the course of Alzheimer's disease (AD). Despite this acknowledged importance, no clearly useful ADL instrument for cross-cultural application in pharmacologic trials in the early stages of AD had been available. Method: An international effort was launched to develop an ADL scale for pharmacologic trials in early AD. Steps taken from 1990 to the present included: (1) international scientific working group meetings and reviews, (2) reviews of existing measures, (3) collating of existent, nonredundant items, (4) querying experts for new items, (5) interviews with informants and subjects in the USA, France, and Germany, toward the identification of potential new items, (6) identification of an item pool based upon these procedures, (7) creation of a trial instrument, (8) piloting of this instrument, and (9) refinement of the scale based upon statistical analysis of the pilot data. Final item selection was based upon: (1) relevance for [greater-than-or-equal] 80% of subjects in severity-stratified USA and German samples; (2) absence of gender and national biases; (3) significant (p < .05) discrimination between (a) normal versus mildly impaired and (b) mildly impaired versus moderately to moderately severely impaired subjects; and (4) Global Deterioration Scale (GDS) scores accounting for [greater-than-or-equal] 12% of variance in the item after controlling for age and gender. Results: An ADL scale consisting of 40 items that correlate with the global and cognitive progress of AD is developed for international usage in pharmacologic trials in incipient, mild, moderate, and moderately severe AD. The scale contains 40 items falling within 13 ADL categories. The 40-item scale is shown to have .81 correlation with GDS staging,.81 with mental status assessment (Mini-Mental State Examination), and .81 with a psychometric test (the SKT) (p values < .001). Conclusion: This scale can be used to measure therapeutic response in AD.